"It has to be designed in a way that really challenges people's assumptions": preparing scholars to build equitable community research partnerships. Issue 1 (20th September 2021) - Tang Yan, Catalina; Haque, Samiya; Chassler, Deborah; Lobb, Rebecca; Battaglia, Tracy; Sprague Martinez, Linda
Abstract: Introduction: Clinical and Translational Award (CTSA) programs are developing relevant training for researchers and community stakeholders participating in community-engaged research (CEnR). However, there is limited research exploring the ways community stakeholders and partners with key CEnR experiences can inform and shape training priorities for prospective CEnR scholars to build meaningful and equitable partnerships. Methods: This study conducted and analyzed online individual semi-structured in-depth interviews with community stakeholders ( n = 13) engaged in CEnR to identify training priorities for graduate students and emerging scholars. Findings: Thematic analysis of 13 interview transcripts revealed four major training priorities for prospective scholars interested in engaging in CEnR: 1) researcher's positionality, 2) equitable power sharing, 3) funding, and 4) ethics. Conclusion: Building equitable research partnerships was a central theme woven across all four training priorities. Further research should focus on examining the development, implementation, and evaluation of CEnR training in partnership with community stakeholders and partners with relevant CEnR experience. Adopting a collaborative approach to incorporate both community stakeholders and researchers' priorities can align training competencies to better prepare scholars to engage in building research partnerships.